Recognition of Sign Language using Capsule Networks - Beser, Fuat; Kizrak, Merve Ayyuce; Bolat, Bulent; Yildirim, Tulay (IEEE, 2018)
Hearing and speech impaired persons continue to communicate with the help of lip reading or hand and face movements also known as a sign language. Ensuring the disabled persons participation in life and increasing their quality of life are achievable through healthy and effective communication with other people. In this work; digits of the sign language were recognized with %94.2 validation accuracy by Capsule Networks.
Keywords: deep learning; deep neural networks; capsule networks; convolutional neural networks; sign language; sign language recognition; Engineering; Telecommunications